-x+2x-2=13

Simple and best practice solution for -x+2x-2=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+2x-2=13 equation:


Simplifying
-1x + 2x + -2 = 13

Reorder the terms:
-2 + -1x + 2x = 13

Combine like terms: -1x + 2x = 1x
-2 + 1x = 13

Solving
-2 + 1x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 1x = 13 + 2

Combine like terms: -2 + 2 = 0
0 + 1x = 13 + 2
1x = 13 + 2

Combine like terms: 13 + 2 = 15
1x = 15

Divide each side by '1'.
x = 15

Simplifying
x = 15

See similar equations:

| 8x^2+43x+15=0 | | 21=7(x)+8 | | 12x-5(2x-7)=-3 | | 8x^2+14x-8=0 | | 3(4-m)=7m+17-2m | | -3=(-1/5)-10 | | 11x-(3x-7)=23 | | 7x+5x-5=3(4x+1) | | 7x-14=3x+18 | | 2x-7=6-6x-2x | | 32/x=x/2 | | 60x-30=15(4x-2) | | (63+9)/3 | | 490=7n | | 3/49=26/7x | | 15z^2+14z-8=0 | | -2y^2+1y+10=0 | | 6(y)-13=-13 | | x^2+8x-12=x^2 | | p-1=5p-8+3p | | 47x+94=47x+81 | | 8.3=4(k)-2.5 | | x^2+8-12=x^2 | | 3+3(2x-1)=14+4x | | 4x-16/3x-12 | | 16m+15m^2-15= | | 3(p)-14=9 | | 7(t)-20=33 | | -14=10-2x | | 8z+12z=5z-21 | | 3x+x+4=8x-4x+4 | | 5(w+4z)-5(w+3)=8 |

Equations solver categories